AWARD SYSTEM IMPROVES ORGANIZATIONAL EFFECTIVENESS IN KECAMATAN KALAWAT MINAHASA UTARA NORTH SULAWESI - Supriati, Arie (Universitas Brawijaya, Indonesia, 2018)
This study aims to examine the extent to which the system of rewards is a solution in improving the effectiveness of organizations in Kalawat District, North Minahasa - North Sulawesi. Given the changing global environment marked by changes in all areas, it is a challenge for an organization to be able to properly utilize the change into an opportunity.Because if it is too late to prepare and develop its potential, then the opportunity will soon be taken more competitor more prepared.The competitive advantage of an organization is determined by external and internal factors. But the internal factor of an organization’s competitive advantage is considered an important factor for success. This research uses the qualitative descriptive approach with literature study method, interview, document and observation at Kalawat District government. The results of this study indicate that rewards are a solution in improving the effectiveness of the organization in the District Government Minahasa North-North Sulawesi.